Continuing education in secondary care: A strategy for the elaboration of the urgency care protocol (Research, Society and Development, 2022)
The work process in the SUS, to be constituted in a way that allows the best interprofessional interaction, requires the daily exercise of Continuing Education in our Health Units. Otherwise, we find ourselves in a multidisciplinary environment, deficient and in need of change, isolated, which can generate lack of encouragement to the professionals involved, and reflecting on SUS users, which should be rethought. In Secondary Care, we found a limited practical activity of Continuing Education in Health, which should be encouraged and experienced in the living process of daily work. This article proposes a reflection on the professional's individual practice, and more than his multidisciplinary interaction in the work process, but at the same time reports a positive experience arising from the performance of Continuing Education in Health Units in the Secondary Care service of the region. mountains of the state of Rio de Janeiro, through the elaboration of a protocol for the care of patients with reduced level of consciousness, adequate to the local reality, product of the demand of the work group.